Quinoline Adsorption Properties of Super-Hydrophilic and Ultra-Light Polyethylene Glycol/Graphene Aerogel - Wengang LYU; Weiwei KANG; Hong ZHAO; Lei QIN; Xuguang LIU; Yongzhen YANG (Taiyuan Ligong Daxue xuebao, 2021)
Polyethylene glycol/graphene aerogel (LPGA) was prepared through the combination of reductive self-assembly and cross-linking induction with L-ascorbic acid as reducing agent and polyethylene glycol as crosslinking agent. This strategy can not only improve the hydrophilicity of LPGA, but also improve its structural stability. The results show that the prepared LPGA possesses advantages of super-hydrophilicity (water contact angle is 0°), ultra-light weight (density is about 6.5 mg/cm3), and outstanding structural stability (bearing about 2 500 times of its own weight). When the LPGA was applied to quinoline adsorption in the solution with an initial concentration of 50 mg/L at 298 K, the equilibrium adsorption capacity of LPGA towards quinoline reached 83.62 mg/g.